Keputusan Nasabah untuk Berinfaq saat Tarik Tunai di ATM (Automatic Teller Mechine) Bank Syariah Indonesia Cabang Jambi - Dini Nurisma; A.A Miftah; Ahmad Syukron Prasaja (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2023)
This study aims to determine the customer's decision to infaq when withdrawing cash at the Jambi Branch BSI ATM, to determine the factors that influence the customer's decision to infaq when withdrawing cash at the Jambi Branch BSI ATM, as well as to determine the response of the Jambi Branch BSI to the decision. Customers in infaq when withdrawing cash at ATM BSI Jambi Branch are different. This type of research is field research. While the nature of this research is descriptive qualitative. Data was collected using interview and documentation techniques. The data from the findings are described descriptively and analyzed using inductive thinking. The results of this study are in the form of factors that influence customer decisions to infaq when withdrawing cash at BSI ATM, namely the transparency factor, the trust factor, and the marketing factor. The transparency factor is that customers still do not know the management structure, how to manage, and distribution of infaq funds. And the marketing factor is that BSI should do more marketing that BSI ATM have infaq products.